THE EFFECT OF KELAKAI (STECHNOLAENA PALUSTRIS) CONSUMPTIONS ON HEMOGLOBIN LEVELS AMONG MIDWIFERY STUDENTS - Gracea Petricka; SN Nurul Makiyah; Retno Mawarti (Belitung Nursing Journal, 2018)
Background: It is estimated that 49.2% of Indonesian adolescents (10-19 years) have iron deficiency of anemia. Green vegetables can be used as an alternative consumption to meet the body's need for iron. Kelakai (Stenochlaena palustris) containing 291.32 mg-100 g of Fe has been consumed by Dayak ethnic society to prevent anemia. Objective: The aim of this study was to determine the effect of Kelakai (Stenochlaena palustris) consumptions to increase hemoglobin levels among late adolescents (17-19 years). Methods: It was a quasi-experiment with pre-test and post-test study on anemic Midwifery students (8-11 g / dl) of Betang Asi Midwifery Academy of Palangka Raya Indonesia in September 2017. In which Kelakai was given as dietary supplements of the subject line and ferrous fumarate tablet as a control. There were 66 participants recruited by purposive sampling, divided into 33 subjects for each group. Kelakai (Stenochlaena palustris) (250 mg) and ferrous fumarate tablet (60 mg) were administrated daily for a week. Hemoglobin levels were measured before and after intervention using the hemoglobin testing system quick-check tool. Data were analyzed using paired and independent t-test. Result: The result showed of significant increases on hemoglobin levels (3.24 g / dl) after consuming Kelakai (Stenochlaena palustris) for a week (p≤0.05). The hemoglobin levels after intervention in the control group were 0.03 g / dl higher than Kelakai group, but based on the analysis, there was no significant difference on both groups (p≥0.05). Conclusion: Kelakai is proven to increase hemoglobin levels. Thus, Kelakai (Stenochlaena palustris) is recommended a food supplementation to prevent iron deficiency of anemia.